2017
DOI: 10.1021/jacs.7b06587
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Monolayer Superlattices of Hollow Mn3O4 Nanocrystals and Their Oxygen Reduction Activity

Abstract: Self-assembled nanocrystal (NC) superlattices are emerging as an important class of materials with rationally modulated properties. Engineering the nanoscale structure of constituent building blocks as well as the mesoscale morphology of NC superlattices is a crucial step in widening their range of applications. Here, we report a template-assisted epitaxial assembly strategy, enabling growth of freestanding, carbon-coated tubular monolayer superlattices (TMSLs). Specifically, we design and construct TMSLs of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 31 publications
4
67
0
1
Order By: Relevance
“…In order to further study the composition and oxidation state of a‐Mn 3 O 4 ONCs, surface composition analysis with X‐ray photoelectron spectroscopy (XPS) measurement was performed (Figure S5a–c, Supporting Information). The results confirmed well that the samples with multiple valences of Mn 2+ and Mn 3+ were successfully fabricated and the binding energy separation of Mn 3s peaks was ≈5.5 eV, which was consistent with that of Mn 3 O 4 reported before …”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…In order to further study the composition and oxidation state of a‐Mn 3 O 4 ONCs, surface composition analysis with X‐ray photoelectron spectroscopy (XPS) measurement was performed (Figure S5a–c, Supporting Information). The results confirmed well that the samples with multiple valences of Mn 2+ and Mn 3+ were successfully fabricated and the binding energy separation of Mn 3s peaks was ≈5.5 eV, which was consistent with that of Mn 3 O 4 reported before …”
Section: Methodssupporting
confidence: 90%
“…A Mn 3 O 4 nanomaterial was selected as an ideal candidate nanomaterial dopant into LCs for improving the E‐O technology, since the outer electrons of Mn 2+ and Mn 3+ were arranged as d 5+ and d 4+ , there were more single electron in the two ionic structures, which produced the charge transfer on the surface much easier among reported semiconductor nanomaterials . The synthesis procedures of hollow amorphous and crystalline Mn 3 O 4 octahedral nanocages (c‐Mn 3 O 4 ONCs) structures were shown in Scheme .…”
Section: Methodsmentioning
confidence: 99%
“…Hard‐template method is a straightforward and universal way to attain hollow interiors using the materials with well‐defined morphologies, such as polymer‐based spheres (e.g., polystyrene (PS), resin, etc. ), MOFs, silica spheres, anodic aluminum oxides (AAO), and other kinds of oxide nanomaterials . In this method, hollow nanomaterials are constructed through shell formation on the templates, which are finally sacrificed partially or completely by selective chemical etching or thermal decomposition.…”
Section: Functionalization Strategies For Synthesis and Catalysis Of mentioning
confidence: 99%
“…Jiao et al demonstrated a pyrolysis method to prepare highly ordered mesoporous few‐layer graphene frameworks with a pore size of ≈10 nm by the carbonization of oleic‐acid‐capped Fe 3 O 4 NP superlattice . As illustrated in Figure , they also applied the same surfactant‐carbonization strategy to prepare tubular assembly of monodisperse hollow MnO@C NPs by conducting the pyrolysis treatment on the AAO‐templated Mn 3 O 4 superlattice . The as‐obtained hollow superlattice showed superior activity (5.7 mA cm −2 for hollow MnO versus 5.8 mA cm −2 for Pt/C at 0.90 V (vs RHE)) and elevated stability toward ORR in basic mediate owing to the hierarchical hollow structure and carbon coating (Figure f,g).…”
Section: Functionalization Strategies For Synthesis and Catalysis Of mentioning
confidence: 99%
“…The main diffraction peaks in XRD spectrum ( Fig. 2A) 23,24 conrming their crystalline nature. Furthermore, the surface of Mn 3 O 4 microspheres was analyzed by XPS.…”
Section: Discussionmentioning
confidence: 98%